2000
DOI: 10.1007/s004390000393
|View full text |Cite
|
Sign up to set email alerts
|

Changes in primary DNA sequence complexity influence the phenotypic consequences of mutations in human gene regulatory regions

Abstract: No general rules have been proposed to account for the functional consequences of gene regulatory mutations. In a first attempt to establish the nature of such rules, an analysis was performed of the DNA sequence context of 153 different single base-pair substitutions in the regulatory regions of 65 different human genes underlying inherited disease. Use of a recently proposed measure of DNA sequence complexity (taking into account the level of structural repetitiveness of a DNA sequence, rather than simply th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…HGMD data have been utilized to study the role that repetitive sequence elements, sequence homologies, and specific motifs play in promoting mutagenesis, and to explore in detail the underlying mutational mechanisms (Krawczak et al, 1998(Krawczak et al, , 2000Ball et al, 2005). HGMD data have been utilized to study the role that repetitive sequence elements, sequence homologies, and specific motifs play in promoting mutagenesis, and to explore in detail the underlying mutational mechanisms (Krawczak et al, 1998(Krawczak et al, , 2000Ball et al, 2005).…”
Section: Suggestions For Further Analysismentioning
confidence: 99%
“…HGMD data have been utilized to study the role that repetitive sequence elements, sequence homologies, and specific motifs play in promoting mutagenesis, and to explore in detail the underlying mutational mechanisms (Krawczak et al, 1998(Krawczak et al, , 2000Ball et al, 2005). HGMD data have been utilized to study the role that repetitive sequence elements, sequence homologies, and specific motifs play in promoting mutagenesis, and to explore in detail the underlying mutational mechanisms (Krawczak et al, 1998(Krawczak et al, , 2000Ball et al, 2005).…”
Section: Suggestions For Further Analysismentioning
confidence: 99%
“…For example, acquiring the ability to relate mutation frequency and position to the characteristics of the local DNA sequence environment could be an invaluable aid to the optimization of mutation search strategies in molecular diagnostic medicine. The study of mutational lesions causing human genetic disease has revealed that, irrespective of their type and nature, mutations are not uniformly distributed along a DNA sequence [Cooper and Krawczak, 1993;Antonarakis et al, 2001] but are instead strongly influenced by the local DNA sequence environment [Krawczak et al, 1998;Krawczak et al, 2000a]. Such meta-analytical studies have provided clear evidence for the existence of endogenous mechanisms of mutation, as distinct from exogenous causes such as radiation or chemical mutagens.…”
Section: Introductionmentioning
confidence: 99%
“…The study of naturally occurring missense mutations on protein-coding genes can be instructive. Even though mutations in a single protein might not be definitively informative because human mutations are not random and are influenced by the local DNA sequence environment (Antonarakis et al 2000;Krawczak et al 2000;Zhang and Gerstein 2003), accumulated occurrences on many functionally related proteins or a group of family members can yield information on the importance of each residue and the underlying functional mechanism.…”
Section: Discussionmentioning
confidence: 99%